2017
DOI: 10.1136/bmjsem-2017-000221
|View full text |Cite
|
Sign up to set email alerts
|

A pilot biomechanical assessment of curling deliveries: is toe sliding more likely to cause knee injury than flatfoot sliding?

Abstract: BackgroundThe aim of this study was to determine whether toe sliding is more likely to cause knee injuries than flatfoot sliding in curling.MethodsTwelve curlers participated in the study, each delivering 12 stones. Six stones per volunteer were delivered using a flatfoot slide and six were delivered using a toe slide. The Pedar-X in-shoe pressure system recorded the plantar pressure during each of the slides, while a sagittal plane digital video recorded the body position of the curler. Measurements were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This analysis occurred via an optotrak certus device (Northern Digital Instruments, Waterloo, ON) and a Curling-Specific Balance Test. Biomechanical force analysis was compared between flat-foot and toe sliding with toe sliding producing a larger moment arm than flat-foot sliding ( 12 ). Three of these studies assessed delivery variables according to movement phases ( 54 , 55 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This analysis occurred via an optotrak certus device (Northern Digital Instruments, Waterloo, ON) and a Curling-Specific Balance Test. Biomechanical force analysis was compared between flat-foot and toe sliding with toe sliding producing a larger moment arm than flat-foot sliding ( 12 ). Three of these studies assessed delivery variables according to movement phases ( 54 , 55 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both acquired a reportive methodology to assess information on the demographics, site of injury, type of injury, and curling-specific aggravated conditions. A supplemental article (cross-referenced from delivery mechanics) addressed injury in terms of biomechanical delivery measurements according to force vector analysis of delivery positions ( 12 ). Studies concluded that curling is a safe winter sport compared to its Winter Olympic sports counterparts ( 13 , 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations